IMPLEMENTASI DAN EFEKTIVITAS BALIHO CAPRES DAN CAWAPRES DALAM KONTESASI PEMILU TAHUN 2024 STUDI KASUS PROVINSI BENGKULU - Susanto, Yohanes; Hairani, Wita (SENGKUNI Journal (Social Science and Humanities Studies), 2024)
This research will discuss how the implementation and effectiveness of billboards for presidential and vice presidential candidates in the 2024 election contestation, case study of Bengkulu Province. In this research, qualitative descriptive research was used. Meanwhile, the data collection technique was to use documentation studies. The main focus of this research is the extent of implementation and effectiveness of billboards for presidential and vice presidential candidates in the 2024 election contestation in the case study of Bengkulu Province.Â Based on this research, research results were obtained which showed that the implementation and effectiveness of billboards for presidential and vice presidential candidates in the 2024 election contestation, case study of Bengkulu Province, that the three 2024 presidential and vice presidential candidate pairs equally won the hearts of the people, as proven by the election contestation through billboard media, the public could recognize and knowing the vision and mission as well as their chosen presidential and vice presidential candidates with the vote count results from the special KPU presidential election survey for Bengkulu Province, the Anies-Muhaimin pair got 19.69% of the votes, the Prabowo-Gibran pair got 69.56% of the votes and while the Ganjar-Mahfud pair got 10, 75% of the vote, and this really gives a positive image in the hearts of the public.